Influenza virus infection exacerbates experimental autoimmune encephalomyelitis disease by promoting type I T cells infiltration into central nervous system. (February 2017) - Chen, Qingyun; Liu, Yinping; Lu, Aizhen; Ni, Ke; Xiang, Zheng; Wen, Kun; Tu, Wenwei
Abstract: Multiple sclerosis starts with increased migration of auto-reactive lymphocytes across the blood-brain barrier, resulting in persistent neurodegeneration. Clinical and epidemiological studies indicated upper respiratory viral infections are associated with clinical exacerbation of multiple sclerosis. However, so far there is no any direct evidence to support it. Using the experimental autoimmune encephalomyelitis mice as the model for multiple sclerosis, we demonstrated that mice experienced with influenza virus infection were unable to recover from experimental autoimmune encephalomyelitis with a long-term exacerbation. The exacerbated disease was due to more type I T cells, such as CD45 high CD4 + CD44 high, CD45 high CD4 + CCR5 +, CD45 high IFNγ + CD4 +, MOG35-55 -specific IFNγ + CD4 + and influenza virus-specific IFNγ + CD4 + T cells, infiltrating central nervous system in mice with prior influenza virus infection. Influenza virus infection created a notable inflammatory environment in lung and mediastinal lymph node after influenza virus inoculation, suggesting the lung may constitute an inflammatory niche in which auto-aggressive T cells gain the capacity to enter CNS. Indeed, the early stage of EAE disease was accompanied by increased CCR5 + CD4 +, CXCR3 + CD4 + T cell and MOG35-55 specific CD4 + T cells localized in the lung in influenza virus-infected mice. CCL5/CCR5 might mediate the infiltration of type I T cells into CNS during the disease development after influenza infection. Administration of CCR5 antagonist could significantly attenuate the exacerbated disease. Our study provided the evidence that the prior influenza virus infection may promote the type I T cells infiltration into the CNS, and subsequently cause a long-term exacerbation of experimental autoimmune encephalomyelitis. Highlights: Mice experienced with influenza virus infection were unable to recover from EAE with a long-term exacerbation. Prior influenza virus infection increased type I T cells in the lung. Prior influenza virus infection promoted the type I T cells infiltration into the CNS. Administration of CCR5 antagonist attenuated the exacerbated disease.